Binder-free copper molecular sieve adsorbent and preparation method thereof
Through the preparation method of the adsorbent without binder, the problems of adsorbent powdering and unstable active ingredients are solved, and the efficient and erosion-resistant CO adsorption effect is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411654741.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
AI Technical Summary
The existing CO copper molecular sieve adsorbents are prone to powder under high frequency pressure changes, and the active ingredient monovalent Cu(I) is unstable, easily transition reduction leads to inactivation, and the core-shell structure adsorbents may rupture when temperature changes.
The preparation method of the adhesive-free copper molecular sieve adsorbent is adopted to prepare spherical granules adsorbent through mechanical mixing, extrusion and granules integrated machine granulation, ball forming and ion exchange steps to ensure uniform material properties and improve the strength and erosion resistance of the adsorbent.
The prepared adsorbent has high strength, erosion resistance, large adsorption capacity, high CO/CH4 separation coefficient, and the CO purity of the product is greater than 99.9%, which is suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical separation, and relates to a CO adsorbent for pressure swing adsorption purification, in particular to a binder-free copper molecular sieve adsorbent and a preparation method thereof. Background Art
[0002] Carbon monoxide (CO) is an important basic chemical raw material and can be used to synthesize many important chemical products, such as acetic acid, formic acid, oxalic acid, dimethylformamide, polycarbonate, polyurethane and various metal carbonyl compounds, etc. It can form industrial chains such as methanol-acetic acid-vinyl acetate, oxalate-ethylene glycol-polyester, and dimethyl carbonate-polycarbonate.
[0003] CO is abundant in sources and can be obtained through coal gasification and natural gas conversion. In addition, many industrial exhaust gases contain a large amount of CO, such as converter gas, blast furnace gas, calcium carbide furnace tail gas, yellow phosphorus furnace gas, etc. CO usually coexists with H2, N2, CH4, CO2 and other impurities. To obtain high-purity CO product gas, gas purification and refining are necessary. Separating and purifying CO can not only serve as an important carbon source for carbon-to-chemical industry, but also play a role in the resource utilization of industrial by-product gas, generating multiple benefits such as economic, social and environmental protection.
[0004] For the separation and purification of CO, the currently mature separation methods are cryogenic separation and pressure swing adsorption (PSA) separation.
[0005] Since the boiling points of CO and N2 are close, the cryogenic separation method is difficult to meet the requirements of high-purity CO in situations where higher requirements are placed on N2. In addition, the synthesis processes of certain fields, such as TDI and ethylene glycol, have very high requirements for CH4 in CO raw materials, usually requiring less than 20ppm. The CO / CH4 separation coefficient of traditional adsorbents is less than 3, which cannot meet the low CH4 requirements.
[0006] Pressure swing adsorption utilizes the adsorption performance of solid adsorbents for different gas components and the characteristic that the adsorption amount changes with pressure, to achieve pressurized adsorption of gas components, decompression and regeneration, and then separation and purification of mixed gases. Compared with traditional cryogenic separation technology, PSA technology for recovering CO from industrial waste gas has obvious advantages in terms of raw gas adaptability, CO product gas quality, production cost and investment, and can provide high-quality and low-cost CO product gas for various carbonyl synthesis chemical industries. The key to the PSA CO purification process is to develop new and efficient CO adsorbents, which require the adsorbents to have high selectivity, large adsorption capacity and erosion resistance. The quality of the adsorbent performance directly determines the quality and cost of the product gas, and is a key factor in the core competitiveness of the PSA CO purification process.
[0007] The key to the PSA method is to develop and manufacture efficient CO adsorbents.
[0008] Commonly used physical adsorbents in PSA process include molecular sieves, activated carbon, silica gel, activated alumina, etc. These physical adsorbents have poor adsorption capacity and selectivity for CO, and the separation coefficients of CO from N2 and CH4 are small, making it difficult to separate CO from a mixture containing CO, CO2, N2 and CH4.
[0009] CO copper molecular sieve adsorbent is a solid complex adsorbent formed by highly dispersing the transition metal ion monovalent Cu(I) that forms a π complex with CO on a zeolite molecular sieve. The theoretical basis for separating CO by π complex adsorption is that CO can form a metal carbonyl complex with Cu(I). The force of complex adsorption is between physical adsorption and chemical adsorption. π bond complex adsorption refers to the formation of a chemical bond between the adsorbate and the adsorbent through π bond complexation. The π bond is not very strong, and the bond energy is generally between 16 and 62 kJ / mol. Therefore, the selectivity of π bond complex adsorption is relatively high and reversible. Through simple process methods, such as reducing the pressure of the system and appropriately raising the temperature, the bond can be broken and the adsorbate can be desorbed. Copper molecular sieve complex adsorbent is the best choice for concentrating CO by PSA method.
[0010] At present, most of the CO copper molecular sieve adsorbents used in industrial applications are strip-shaped particles. Since pressure swing adsorption involves a series of process steps such as adsorption, pressure equalization, forward release, displacement, reverse release, and evacuation, each process requires a programmable valve switch to achieve pressure change. Frequent pressure changes cause erosion of the adsorbent, and the cross-section of the strip-shaped particles is prone to pulverization under high-frequency erosion.
[0011] Chinese invention patent CN86102838 discloses a highly efficient adsorbent and its preparation method and use. CuCl is mixed with 13X, NaY molecular sieve and other carriers with high specific surface area to prepare highly efficient CO adsorbent by extrusion. It has been successfully applied to PSA separation of CO. The purity of the obtained gas is greater than 99%. Because the adsorbent is formed by extrusion, there is a serious problem of adsorbent powdering in many industrial devices.
[0012] Chinese invention patent CN96117226.6 discloses a catalyst for purifying carbon monoxide in nitrogen-containing gas, which is made of copper chloride, activated carbon, natural high-quality attapulgite and mixed rare earth chloride by impregnation or / and mixing, and is used for purifying trace carbon monoxide in nitrogen-containing gas by temperature swing adsorption or pressure swing adsorption process. However, it is not suitable for separation and purification of high CO concentration in industrial tail gas.
[0013] Chinese invention patent CN103566809 discloses a copper-containing molecular sieve adsorbent and a preparation method thereof. NaY molecular sieve, sesbania powder and clay are mixed and ball-milled and then extruded into strips to form a carrier. Copper acetate and glucose are dissolved in water to form a solution, and the prepared solution is used to impregnate the carrier to prepare the adsorbent.
[0014] Chinese invention patent CN115722187 discloses a high adsorption capacity carbon monoxide complex adsorbent and its preparation method and application. It uses Y-type or X-type molecular sieve as a carrier, first obtains divalent copper-exchanged Cu(II)Y or Cu(II)X through ion exchange, then uses solid-state thermal dispersion method to load CuCl, and then obtains CO-loaded copper adsorbent after reduction.
[0015] The active ingredient of copper molecular sieve adsorbent is monovalent Cu(I), which is unstable and undergoes the following reaction in the air: 6CuCl+1.5O2+3H2O→2Cu3Cl2(OH)4+CuCl2. The reduction process needs to be controlled before use, as it is easy to be excessively reduced to O-valent Cu(0), causing irreversible deactivation of the adsorbent and loss of adsorption performance.
[0016] Chinese invention patent CN116809040 discloses a core-shell structure carbon monoxide adsorbent and its preparation method, which is prepared by a mechanical rolling ball method using microspheres with high specific heat and non-porous structure modified by a silane coupling agent as the core and a molecular sieve loaded with cuprous salt as the shell, and then reduced with H2 or CO to obtain the adsorbent.
[0017] Chinese invention patent CN117065717 discloses a composite adsorbent for pressure swing adsorption separation of carbon monoxide with a core-shell structure. The adsorbent is prepared by a coating process and then reduced with H2 or CO, using microspheres with high specific heat and non-porous structure as the core and a molecular sieve exchanged with divalent copper loaded with cuprous salt as the shell.
[0018] In order to make the complex adsorbed CO easy to decompose, the operating temperature of the copper molecular sieve adsorbent is usually between 60-90℃. If the operating temperature is too low, the π bond is not easy to break, the desorption amount of CO adsorbed by the adsorbent is small, the adsorbent utilization rate is insufficient, and the operating temperature is too high. H2 or CO in the process raw gas will cause the adsorbent to transition and lose its activity. The copper molecular sieve adsorbent is always accompanied by changes in temperature and pressure during actual industrial applications. This requires that the material of the adsorbent must be uniform during the preparation process, and the core and shell will not break due to the difference in expansion coefficient during the temperature change process. The core-shell structure adsorbent disclosed in China's invention patent CN116809040 and China's invention patent CN117065717 has the possibility of spherical particles breaking during use due to the inconsistent performance of the materials coated on the core and outer layer.
[0019] The operating temperature of pressure swing adsorption for purifying CO by copper molecular sieve adsorbent is between 60-90℃. The process includes a series of processes such as adsorption, equal pressure drop, forward discharge, displacement, reverse discharge, evacuation, equal pressure rise, and final filling. Each process requires a program-controlled valve switch to achieve pressure changes. Frequent pressure changes are accompanied by changes in gas flow rate and temperature in the adsorption tower, which puts high demands on the mechanical properties, erosion resistance, and thermal stability of the adsorbent. At present, most adsorbents used in industry are formed by extrusion, and the cross-section of strip particles is easily pulverized under high-frequency erosion. Due to the strong corrosiveness of cuprous chloride, the pulverized adsorbent powder causes serious damage to subsequent pipelines and equipment. Summary of the invention
[0020] The purpose of the present invention is to avoid at least one of the shortcomings of the above-mentioned prior art and provide a method for preparing a copper molecular sieve adsorbent suitable for large-scale industrial production; the adsorbent prepared by the method has high strength, erosion resistance, large adsorption capacity, and good stability of the active component cuprous chloride.
[0021] In order to achieve the purpose of the present invention, the specific technical scheme of the present invention is as follows:
[0022] A preparation method of a binder-free copper molecular sieve adsorbent comprises the following steps: mixing clay, molecular sieve, cuprous chloride and a bonding aid to prepare a raw powder material; taking part of the raw powder material, adding water and kneading, granulating by using an extruder and pelletizer, and then placing the particles in a ball rolling machine to roll and ball, adding the raw powder material during the ball rolling process to make the balls grow, and preparing spherical adsorbent precursor particles after drying and roasting; finally, performing ion exchange on the adsorbent precursor particles with a monovalent copper salt solution, and then drying and roasting to prepare the binder-free copper molecular sieve adsorbent.
[0023] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, the raw powder material includes the following components in parts by weight: 1 to 40 parts of clay, 5 to 50 parts of molecular sieve, 10 to 50 parts of cuprous chloride, and 1 to 10 parts of a bonding aid.
[0024] Further, in the preparation method of the binder-free copper molecular sieve adsorbent, the clay is selected from one or two of kaolin, activated clay, attapulgite, diatomite, bentonite and argillaceous earth; the molecular sieve is selected from one of 13X, NaY and USY; the bonding aid is selected from one of carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol, polypropylene alcohol and dextrin; the bonding aid will be completely decomposed during the calcination of the adsorbent precursor and does not occupy the weight percentage of the adsorbent. The monovalent copper salt solution is a cuprous chloride solution dissolved in concentrated hydrochloric acid.
[0025] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, when preparing the raw powder material, mechanical mixing is used, the mixing time is 10-60 minutes, and the mixer speed is 10-60 rpm. The purpose of mixing is to achieve full contact between various materials.
[0026] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, after the mixing is completed, a part of the mixed raw powder material is added to a certain amount of deionized water for kneading, and the amount of water added is sufficient to ensure that the material is easy to extrude and has a smooth surface. The mixed material is made into particles with a diameter of 1.0 to 1.5 mm and a length of 1.0 to 1.5 mm using an extrusion and pelletizing integrated machine. The active ingredient cuprous chloride accounts for a high proportion in the copper molecular sieve adsorbent, and the cuprous chloride has a high specific gravity, while the molecular sieve has a light specific gravity. Due to the material characteristics, the balling rate of the rolling method using conventional molecular sieves such as 5A and 13X, which is gradually rolled from the raw powder granulation, is low, the seed density is insufficient, and the strength is difficult to meet the requirements of the adsorbent industrial application. The seed particles prepared by the extrusion and pelletizing integrated machine have high strength, and the seeds are consistent with the later rolling materials. The use of mixed raw powder extrusion granulation and then rolling growth is one of the characteristics of the adsorbent production method of the present invention.
[0027] The extrusion and pelletizing machine is a commercially available mature industrial product. For example, Chinese utility model CN215540653U discloses an extrusion and pelletizing machine for alumina carrier molding, Chinese utility model CN219334113U discloses an extrusion and pelletizing machine for alumina carrier molding, and Chinese utility model CN204431552U discloses a pelletizing mechanism and an extrusion and pelletizing device using the pelletizing mechanism.
[0028] The particles prepared by extrusion are sieved to remove powder and then placed in a ball rolling machine to form balls. During the ball rolling process, the above-mentioned raw powder mixture is added to the balls for rolling and enlargement. The extruded particles and the balls are made of the same material, so the uniformity of the material properties is ensured, and the core-shell structure adsorbent will not rupture due to inconsistent core-shell materials and different expansion coefficients.
[0029] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, the extruded particles are placed in a ball rolling machine to form spherical particles of 2.0-4.0 mm; the ball rolling machine uses a special-shaped sugar coating pan, a pear-shaped sugar coating pan or a disc granulator, and the speed of the ball rolling machine during the ball rolling process is 20-50 rpm.
[0030] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, the amount of cuprous chloride added to the cuprous chloride hydrochloric acid solution is 10-50% of the weight percentage of the adsorbent precursor particles; the molar ratio of cuprous chloride to concentrated hydrochloric acid during the dissolution of cuprous chloride is 1:1; the exchange temperature of the copper salt solution and the adsorbent precursor ions is 40-90°C, and the exchange time is 2-24h.
[0031] Through ion exchange, the cations in the clay added during the preparation of the adsorbent precursor are exchanged with monovalent Cu(I) ions and have adsorption properties, which greatly improves the adsorption capacity of the adsorbent and realizes the conversion of the binder.
[0032] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, the drying temperature of the adsorbent precursor particles is 100-200° C., the drying time is 2-10 hours, and the calcination temperature is 300-500° C., and the calcination time is 2-10 hours.
[0033] Furthermore, in the preparation method of the binder-free copper molecular sieve adsorbent, the drying temperature of the adsorbent after ion exchange is 100-200° C., the drying time is 2-10 hours, and the calcination temperature is 300-500° C., and the calcination time is 4-8 hours.
[0034] The present invention also protects an adsorbent obtainable by any one of the above preparation methods or any combination of preparation steps.
[0035] Furthermore, the present invention also protects the use of the adsorbent prepared by the above method, wherein the adsorbent is used for the pressure swing adsorption of mixed gas containing CO to concentrate CO, and the adsorbent is reduced with H2 or CO before use; the reduction temperature is 90-160°C, and the adsorbent particles are used to obtain a CO product gas with a concentration greater than 99.9%. The reduction endpoint judgment standard is that the content of the raw gas entering and leaving the adsorption tower is close.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The adsorbent prepared by the method is a spherical particle, which is prepared by a method combining extrusion granulation, ball rolling and ion exchange, and overcomes the shortcomings of powdering caused by the cross section of the strip particles and poor thermal stability of the spherical core-shell structure adsorbent. The adsorbent is used for pressure swing adsorption to purify CO, and more than 20% of CO in the mixed gas can be concentrated by the pressure swing adsorption process to obtain a CO product gas with a concentration greater than 99.9%, and the CO yield is greater than 91%.
[0038] (2) The adsorbent prepared by this method has high strength and is resistant to erosion;
[0039] (3) In the preparation method, the added binder is made binder-free after cuprous chloride ion exchange;
[0040] (4) The copper molecular sieve adsorbent of the present invention uses monovalent cuprous chloride as the active ingredient during the preparation process, and only a very small amount of it is oxidized during the preparation process. The reduction time during industrial application is 50-70% shorter than that of adsorbents prepared by other methods, which can greatly save the initial operating cost of the production device.
[0041] (5) The adsorbent prepared by this method has a large adsorption capacity and a high CO / CH4 separation coefficient;
[0042] (6) The preparation method is simple and suitable for large-scale industrial production. DETAILED DESCRIPTION
[0043] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0044] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0045] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0046] In the present application, 1 part means 1 part by weight, which can be regarded as 1 kg or 1 g.
[0047] Embodiment 1:
[0048] 1 part of kaolin, 50 parts of 13X molecular sieve, 39 parts of cuprous chloride and 10 parts of carboxymethyl cellulose were mechanically mixed in a mixer for 10 minutes; the mixer speed was 60 rpm. Take part of the mixed raw powder material and add water to knead. The amount of water added should ensure that the material is easy to extrude and the surface is smooth. Use an extrusion and pelletizing machine to make particles with a diameter of 1.0 mm and a length of 1.5 mm. After sieving and removing the powder from the extruded particles, the particles are placed in a special-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry material is added, and the balls are made into 2.0 mm spherical particles. The ball rolling machine speed during the rolling process is 20 rpm. The adsorbent spherical particles after rolling are dried at 200°C for 2 hours, and then roasted at 500°C for 2 hours to obtain an adsorbent precursor (particles).
[0049] Take 20% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 40°C, and the exchange time is 24h. The adsorbent after ion exchange is dried at 200°C for 2h, and then roasted at 500°C for 4h to prepare an adsorbent product, numbered CA-01.
[0050] Comparative Example 1:
[0051] 1 part of kaolin, 50 parts of 13X molecular sieve, 39 parts of cuprous chloride and 10 parts of carboxymethyl cellulose were mechanically mixed in a mixer for 10 minutes; the mixer speed was 60 rpm. Take part of the mixed raw powder material, add water and knead, and use an extruder and pelletizer to make particles with a diameter of 1.0 mm and a length of 1.5 mm. After sieving and removing the powder from the extruded particles, the particles were placed in a special-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials were added, and the balls were made into 2.0 mm spherical particles. The balling machine speed during the rolling process was 20 rpm. The spherical particles of the adsorbent after rolling were dried at 200°C for 2 hours, and then calcined at 500°C for 2 hours to obtain the adsorbent. No. CB-01.
[0052] Example 2
[0053] 40 parts of activated clay, 5 parts of NaY molecular sieve, 50 parts of cuprous chloride and 5 parts of hydroxyethyl cellulose were mechanically mixed in a mixer for 60 minutes; the mixer speed was 10 rpm. Part of the mixed raw powder material was added to water and kneaded, and particles with a diameter of 1.5 mm and a length of 1.0 mm were made using an extrusion and pelletizing machine. The particles prepared by extrusion were sieved to remove the powder, and then placed in a special-shaped pear-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials were added, and the balls were made into 4.0 mm spherical particles. The balling machine speed during the rolling process was 60 rpm. The adsorbent spherical particles after rolling were dried at 100°C for 10 hours, and then calcined at 300°C for 10 hours to obtain the adsorbent precursor.
[0054] Take 10% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and make cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 90°C, and the exchange time is 2h. The adsorbent after ion exchange is dried at 100°C for 10h, and then roasted at 300°C for 8h to make an adsorbent product, numbered CA-02.
[0055] Comparative Example 2:
[0056] 40 parts of activated clay, 5 parts of NaY molecular sieve, 50 parts of cuprous chloride and 5 parts of hydroxyethyl cellulose were mechanically mixed in a mixer for 60 minutes at a mixer speed of 10 rpm.
[0057] The mixed raw powder material was added with water and kneaded, and was made into strip-shaped particles with a diameter of 4.0 mm by using an extruder and pelletizer. The adsorbent precursor was obtained by drying at 100°C for 10 hours and then calcining at 300°C for 10 hours.
[0058] Take 10% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and make cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 90°C, and the exchange time is 2h. The adsorbent after ion exchange is dried at 100°C for 10h, and then roasted at 300°C for 8h to make an adsorbent product, numbered CB-02.
[0059] Embodiment 3:
[0060] 39 parts of attapulgite, 50 parts of USY molecular sieve, 10 parts of cuprous chloride and 1 part of polyvinyl alcohol were mechanically mixed in a mixer for 20 minutes; the mixer speed was 50 rpm. Take part of the mixed raw powder material, add water and knead, and use an extruder and pelletizer to make particles with a diameter of 1.1 mm and a length of 1.4 mm. The particles prepared by extrusion were sieved to remove the powder and then placed in a pear-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials were added, and the balls were made into 2.5 mm spherical particles. The balling machine speed during the rolling process was 30 rpm. The spherical particles of the adsorbent after rolling were dried at 110°C for 8 hours, and then calcined at 400°C for 5 hours to obtain the adsorbent precursor.
[0061] Take 50% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 80°C, and the exchange time is 5h. The adsorbent after ion exchange is dried at 110°C for 8h, and then roasted at 400°C for 5h to prepare an adsorbent product, numbered CA-03.
[0062] Comparative Example 3:
[0063] 39 parts of attapulgite, 50 parts of USY molecular sieve, 10 parts of cuprous chloride and 1 part of polyvinyl alcohol were mechanically mixed in a mixer for 20 minutes at a mixer speed of 50 rpm.
[0064] After mixing, part of the raw powder material was added with water and kneaded, and spherical particles with a diameter of 2.5 mm were made by an extruder and pelletizer, dried at 110°C for 8 hours, and then calcined at 400°C for 5 hours to obtain an adsorbent. No. CB-03.
[0065] Embodiment 4:
[0066] 20 parts of diatomaceous earth, 25 parts of 13X molecular sieve, 50 parts of cuprous chloride and 6 parts of polypropylene alcohol were mechanically mixed in a mixer for 30 minutes; the mixer speed was 40 rpm. Take part of the mixed raw powder material, add water and knead, and use an extrusion and pelletizing machine to make particles with a diameter of 1.2 mm and a length of 1.3 mm. The particles prepared by extrusion are sieved to remove the powder, and then the particles are placed in a disc granulator for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry material is added, and the balls are rolled to form 3.0 mm spherical particles. During the rolling process, the ball rolling machine speed is 40 rpm. The spherical particles of the adsorbent after rolling are dried at 150°C for 6 hours, and then calcined at 450°C for 3 hours to obtain the adsorbent precursor.
[0067] Take 10% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and make cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 70°C, and the exchange time is 10h. The adsorbent after ion exchange is dried at 150°C for 6h, and then roasted at 450°C for 3h to make an adsorbent product, numbered CA-04.
[0068] Embodiment 5:
[0069] 30 parts of bentonite, 33 parts of NaY molecular sieve, 30 parts of cuprous chloride and 7 parts of dextrin were mechanically mixed in a mixer for 40 minutes; the mixer speed was 30 rpm. Take part of the mixed raw powder material, add water and knead, and use an extruder and pelletizer to make particles with a diameter of 1.3 mm and a length of 1.2 mm. After sieving and removing the powder, the particles prepared by extrusion are placed in a pear-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials are added, and the balls are made into 2.0 mm spherical particles. During the rolling process, the ball rolling machine speed is 50 rpm. The spherical particles of the adsorbent after rolling are dried at 180°C for 3 hours, and then roasted at 320°C for 9 hours to obtain the adsorbent precursor.
[0070] Take 30% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 60°C, and the exchange time is 15h. The adsorbent after ion exchange is dried at 180°C for 3h, and then roasted at 320°C for 7h to prepare an adsorbent product, numbered CA-05.
[0071] Embodiment 6:
[0072] 37 parts of arginine, 40 parts of USY molecular sieve, 20 parts of cuprous chloride and 3 parts of hydroxyethyl cellulose were mechanically mixed in a mixer for 50 minutes; the mixer speed was 20 rpm. Take part of the mixed raw powder material and add water to knead, and use an extruder and pelletizer to make particles with a diameter of 1.4 mm and a length of 1.1 mm. After sieving and removing the powder, the particles prepared by extrusion are placed in a special-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials are added, and the balls are made into 3.7 mm spherical particles. The ball rolling machine speed during the rolling process is 35 rpm. The spherical particles of the adsorbent after rolling are dried at 130°C for 7 hours, and then roasted at 350°C for 8 hours to obtain the adsorbent precursor.
[0073] Take 40% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 50°C, and the exchange time is 20h. The adsorbent after ion exchange is dried at 130°C for 7h, and then roasted at 350°C for 6h to prepare an adsorbent product, numbered CA-06.
[0074] Embodiment 7:
[0075] 20 parts of kaolin, 16 parts of bentonite, 10 parts of NaY molecular sieve, 45 parts of cuprous chloride and 9 parts of polyvinyl alcohol were mechanically mixed in a mixer for 25 minutes; the mixer speed was 15 rpm. Take part of the mixed raw powder material and add water to knead, and use an extrusion and pelletizing machine to make particles with a diameter of 1.5 mm and a length of 1.5 mm. The particles prepared by extrusion are sieved to remove the powder and then placed in a disc granulator for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry material is added, and the balls are made into 2.8 mm spherical particles. The balling machine speed during the rolling process is 25 rpm. The adsorbent spherical particles after rolling are dried at 160°C for 5 hours, and then calcined at 380°C for 7 hours to obtain the adsorbent precursor.
[0076] Take 15% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 65°C, and the exchange time is 13h. The adsorbent after ion exchange is dried at 160°C for 5h, and then roasted at 380°C for 5h to prepare an adsorbent product, numbered CA-07.
[0077] Embodiment 8:
[0078] 5 parts of attapulgite, 5 parts of activated clay, 45 parts of 13X molecular sieve, 40 parts of cuprous chloride and 5 parts of carboxymethyl cellulose were mechanically mixed in a mixer for 35 minutes; the mixer speed was 35 rpm. Take part of the mixed raw powder material, add water and knead, and use an extrusion and pelletizing machine to make particles with a diameter of 1.0 mm and a length of 1.0 mm. After sieving and removing the powder from the extruded particles, the particles were placed in a special-shaped sugar coating pan for rolling and balling. During the rolling process, the above-mentioned mixed raw powder dry materials were added, and the balls were made into 2.2 mm spherical particles. During the rolling process, the ball rolling machine speed was 45 rpm. The spherical particles of the adsorbent after rolling were dried at 120°C for 9 hours, and then calcined at 430°C for 4 hours to obtain the adsorbent precursor.
[0079] Take 20% of the above precursor by weight of cuprous chloride and dissolve it in concentrated hydrochloric acid solution, the molar ratio of cuprous chloride to concentrated hydrochloric acid is 1:1, and prepare cuprous chloride hydrochloric acid solution. The prepared adsorbent precursor particles are ion exchanged with the cuprous chloride hydrochloric acid solution, the ion exchange temperature is 75°C, and the exchange time is 8h. The adsorbent after ion exchange is dried at 120°C for 9h, and then roasted at 430°C for 4h to prepare an adsorbent product, numbered CA-08.
[0080] Embodiment 9:
[0081] This example is the copper molecular sieve adsorbent prepared in Examples 1-8 and Comparative Examples 1-3, and its main physicochemical properties and adsorption properties are analyzed, tested and evaluated.
[0082] The adsorbent is loaded in a fixed bed adsorber, and the loading amount is 100ml. The adsorbent is reduced with reducing gas before testing. The reducing gas composition is 1.88v% CO, and the rest is N2. The reduction temperature is 90-160°C. Before the test, the adsorption bed is pressurized with argon to the pressure required for the test. The mixed gas passes through the adsorption bed, and the CO therein is selectively adsorbed. The hydrogen content of the raw gas used is 64% (volume percentage, the same below), the carbon monoxide content is 23%, the methane content is 8%, and the nitrogen content is 5%. The test temperature is 70°C, the test pressure is 0.5MPa, and the outlet of the adsorber is detected by a CO infrared analyzer. When the CO concentration at the outlet of the adsorber reaches 0.1%, the detection is stopped, and it is considered that the adsorbent is penetrated. Use a vacuum pump to evacuate to -80~-90kPa at room temperature for desorption. The desorption amount is measured to calculate the adsorption amount of the adsorbent.
[0083] For comparison, the physical adsorbent 5A molecular sieve used in normal temperature pressure swing adsorption was tested under the same conditions.
[0084] Table 1 Adsorbent adsorption capacity test results
[0085] Adsorbent No. Strength N / particle Wear rate% Breakthrough adsorption ml / g <![CDATA[CO / CH4 separation coefficient]]> Product CO purity % CA-01 32.3 0.23 33.7 22.5 99.91 CB-01 32.3 0.23 26.3 7.8 98.42 CA-02 45.7 0.19 34.5 19.2 99.93 CB-02 23.9 2.36 36.8 19.8 99.54 CA-03 37.4 0.22 34.4 21.5 99.92 CB-03 18.8 2.75 28.2 9.2 98.67 CA-04 34.5 0.25 35.5 23.7 99.95 CA-05 36.3 0.25 36.3 22.1 99.93 CA-06 41.2 0.21 33.6 21.6 99.93 CA-07 39.1 0.18 32.4 19.6 99.92 CA-08 33.2 0.24 34.6 23.4 99.94 5A molecular sieve 30.6 0.21 6.5 2.8 85.22
[0086] It can be seen from the test results in Table 1 that the adsorbent of the present invention is binder-free after ion exchange, and the adsorption capacity and CO / CH4 separation coefficient are greatly improved compared with no exchange. The spherical copper molecular sieve adsorbent of the present invention has a large adsorption capacity and high strength; the product CO purity is greater than 99.9%, and it is an ideal adsorbent for purifying CO from industrial tail gas.
[0087] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
[0088] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A method for preparing a binder-free copper molecular sieve adsorbent, characterized in that The following steps are involved: Clay, molecular sieve, cuprous chloride and a bonding agent are mixed to prepare a raw powder material; a portion of the raw powder material is added to water for kneading, granulated by an extruder and pelletizer, and then the particles are placed in a ball rolling machine for rolling and balling, and the raw powder material is added during the ball rolling process to make the balls grow, and then spherical adsorbent precursor particles are prepared after drying and roasting; finally, the adsorbent precursor particles are ion exchanged with a monovalent copper salt solution, and then dried and roasted to prepare a binder-free copper molecular sieve adsorbent; the raw powder material comprises the following components in parts by weight: 1 to 40 parts of clay, 5 to 50 parts of molecular sieve, 10 to 50 parts of cuprous chloride, and 1 to 10 parts of a bonding agent.
2. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 1, characterized in that: The clay is selected from one or two of kaolin, activated clay, attapulgite, diatomaceous earth, bentonite and argillaceous earth; the molecular sieve is selected from one of 13X, NaY and USY; the bonding aid is selected from one of carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol, polypropylene alcohol and dextrin; and the monovalent copper salt solution is a cuprous chloride solution dissolved in concentrated hydrochloric acid.
3. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 1 or 2, characterized in that: When preparing the raw powder material, mechanical mixing is adopted, the mixing time is 10-60 minutes, and the mixer speed is 10-60 revolutions per minute.
4. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 3, characterized in that: The mixed materials are made into particles with a diameter of 1.0 to 1.5 mm and a length of 1.0 to 1.5 mm by an extrusion and pelletizing integrated machine.
5. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 1, 2 or 4, characterized in that: The extruded particles are placed in a ball rolling machine to form spherical particles of 2.0-4.0 mm; the ball rolling machine is a special-shaped sugar coating pan, a pear-shaped sugar coating pan or a disc granulator, and the speed of the ball rolling machine is 20-50 rpm during the ball rolling process.
6. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 5, characterized in that: The amount of cuprous chloride added to the cuprous chloride hydrochloric acid solution is 10-50% of the weight percentage of the adsorbent precursor particles; the molar ratio of cuprous chloride to concentrated hydrochloric acid during the dissolution of cuprous chloride is 1:1; the exchange temperature of the copper salt solution and the adsorbent precursor ions is 40-90°C, and the exchange time is 2-24h.
7. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 1, 2, 4 or 6, characterized in that: The drying temperature of the adsorbent precursor particles is 100-200° C., the drying time is 2-10 hours, the calcination temperature is 300-500° C., and the calcination time is 2-10 hours.
8. The method for preparing the binder-free copper molecular sieve adsorbent according to claim 7, characterized in that: The drying temperature of the adsorbent after ion exchange is 100-200° C., the drying time is 2-10 hours, and the calcination temperature is 300-500° C., and the calcination time is 4-8 hours.
9. An adsorbent obtained by the preparation method as described in any one of claims 1, 2, 4, 6 or 8.
10. The use of the adsorbent according to claim 9, characterized in that: The adsorbent is used for CO-containing mixed gas pressure swing adsorption to concentrate CO. The adsorbent is reduced with H2 or CO before use; the reduction temperature is 90-160°C, and the adsorbent particles are used to obtain a CO product gas with a concentration greater than 99.9%.
Citation Information
Patent Citations
Catalyst for purifying nitrogen-contained gas to remove carbon monoxide and course thereof
CN1185353A
Granulation mechanism as well as extrusion and granulation device using same
CN204431552U
Strip extruding and pelletizing all-in-one machine for forming aluminum oxide carrier
CN215540653U
Strip extruding and pelletizing all-in-one machine for forming aluminum oxide carrier
CN219334113U
High efficiency adsorbent, and preparation and uses thereof
CN86102838B